Laparoscopic adrenalectomy - Tsuru Nobuo; Suzuki Kazuo (Journal of Minimal Access Surgery, 2005)
Laparoscopic adrenalectomy is currently recognized as the gold standard for the treatment of adrenal tumors. In order to assess the current status of laparoscopic adrenalectomy, we reviewed the literature focusing on the indications and contraindications, surgical techniques, complications and new methods. We also reviewed the results separately for aldosteronoma, pheochromocytoma, Cushing′s syndrome, and primary or metastatic adrenal cancer. Laparoscopic adrenalectomy is a safe and effective treatment for adrenal disorders, excluding primary adrenal cancer. There are no differences of the various operative parameters between the transperitoneal and retroperitoneal approaches, so the choice of approach should depend on the surgeon′s preference or the patient′s circumstances. It is important for the surgeon to remove the tumor and the surrounding fat en bloc, especially in the case of large or irregular tumors because of the potential for malignancy. The surgeon must also immediately switch to an open procedure if the laparoscopic operation becomes difficult. We conclude that use of laparoscopic adrenalectomy allows the performance of minimally invasive surgery with the advantages of more rapid recovery and a shorter hospital stay than open adrenalectomy.